Catalytic ceramic membrane integrated with granular activated carbon for efficient removal of organic pollutants. (June 2022) - Wang, Songxue; Wu, Qianqian; Huang, Rui; Guo, Yuan; Yan, Boyin; Hao, Xiujuan; Li, Jincheng; Xia, Wenxiang; Tian, Jiayu
Abstract: A hybrid process of catalytic ceramic membrane integrated with granular activated carbon (GAC) was proposed for removal of organic pollutants in water. By coating flat-sheet ceramic membrane with Co oxide and loading GAC into membrane channels, the integrated catalytic ceramic membrane module (MCo -GAC) with peroxymonosulfate (PMS) activation and GAC adsorption was successfully prepared. The decontamination performance of the MCo -GAC/PMS system was systematically investigated by using bisphenol A (BPA) as target pollutant. Excellent removal efficiency of the MCo -GAC/PMS system was achieved, and hydroxyl radicals ( OH) and sulfate radicals (SO4 − ) were identified as the major reactive species responsible for the degradation process. The MCo -GAC/PMS system showed strong resistance to humic acid (HA) and various anions for BPA removal. Moreover, the MCo -GAC/PMS system exhibited excellent universality for various organic pollutants, where MCo -GAC had superior stability and reusability. The integrated process provides a proposed strategy for enhancing the remediation of organic pollutants. Graphical abstract: Unlabelled Image Highlights: A hybrid process of catalytic ceramic membrane integrated with GAC was designed and developed. The integrated system substantially improved the removal efficiency of organic pollutants. Great adaptability of the integrated system in presence of various background factors. The integrated system exhibited excellent reusability and sustainability.